A Case Report of Adenocarcinoma in Barrett-like Esophagus after Total Resection of the Gastric Remnant - Konishi, Masaru; Tachimori, Yuji; Itabashi, Masayuki; Yamaguchi, Hajime; Hirota, Teruyuki; Ishikawa, Tsutomu; Kato, Hoichi; Watanabe, Hiroshi (Nippon Shokaki Geka Gakkai zasshi, 1991)
A case of adenocarcinoma in Barrett-like esophagus after total resection of the gastric remnant is reported. A 52-year-old man underwent distal gastrectomy for gastric cancer at 33 years of age and total resection of the gastric remnant for cancer of the remnant at 35 age. Because of reflux esophagitis, endoscopy revealed Barrett-like esophagus in April 1983, when he was 45. Furthermore, superficial type esophageal carcinoma was detected in Barrett-like esophagus in December 1989. A subtotal esophagectomy was performed on January 19, 1990. A 7.4×3.2 cm lesion in the lower esophagus showed plateau elevation. The histological type was well differentiated adenocarcinoma and the invasion was limited to the muscularis mucosae. There were no metastases in the 44 dissected lymph nodes. Its mucin and clinicopathological features were similar to well-differentiated adenocarcinoma in the stomach.